(untitled) (Journal of Ideas in Health, 2023)
Background: Non-steroidal anti-inflammatory drugs are commonly used medications with atypical pharmacological effects. This aims to evaluate the anxiolytic-like effects of flurbiprofen in rodent models. Methods: In vivo experimental try was conducted from October 2022 to January 2023 at the college of veterinary medicine, university of Mosul, Iraq. The effect of flurbiprofen was assessed in mice exposed to the elevated plus maze (EPM), light-dark box test (LDT), and open-field test (OFT). Fifty male mice were divided into two groups of twenty-five, weighing 30–35 g, for acute and chronic treatment. Each group was subdivided into five subgroups: distilled water was administered to the control group; the positive control was injected with 10 mg/kg diazepam; and the flurbiprofen groups were administered orally at 10, 20, and 40 mg/kg. Each subgroup was subjected to EPM, LDT, and OFT one hour after administration. The second group was also subdivided like the first group. It was treated for 15 days constantly and subjected to anxiety tests on the 16th day. Results: Acute treatment with 20 mg/kg flurbiprofen revealed an anxiolytic effect, with increased time spent in the open arm of the EPM test, increased time spent in the LDB test, and increased time spent in the central area in the OFT compared to the control group. Chronic administration of flurbiprofen was ineffective in producing an anxiolytic effect. Conclusion: The low doses of flurbiprofen may eliminate the anxiety effect in experimental mice; however, the anti-anxiety effect does not appear significantly after repeated or chronic administration of flurbiprofen.